A regional approach for infection prevention in death investigations during the COVID-19 era. (February 2021) - Nakamura, Mami; Tojo, Misa; Takaso, Marin; Hitosugi, Masahito
Highlights: Postmortem procedures in the COVID-19 era require infection prevention. Postmortem PCR can be used to determine infection risk. Forensic medical examiners and clinicians proactively test cadavers for COVID-19. A fluent updating of examining system would be required.